Hyperbaric intervention ameliorates the negative effects of long-term high-altitude exposure on cognitive control capacity - Ren, Hong; Zhu, Yun-Peng; Su, Rui; Li, Hao; Pan, Yong-Yue (Frontiers in Physiology, 2024)
Hypoxia due to reduced partial pressure of oxygen from high-altitude exposure affects the cognitive function of high-altitude migrants. Executive function is an important component of human cognitive function, characterized by high oxygen consumption during activity, and its level can be measured using cognitive control capacity (CCC). In addition, there is evidence for the potential value of hyperbaric oxygen (HBO) interventions in improving cognitive decline on the plateau. Therefore, the objective of this study was to investigate the effect of long-term high-altitude exposure on CCC in high-altitude newcomers and whether hyperbaric oxygen intervention has an ameliorative effect.Methods: This study measured the magnitude of participants' CCC using a Backward Masking Majority Function Task (MFT-M). Study 1 was a controlled study of different altitude conditions, with 64 participants in the high-altitude newcomer group and 64 participants in the low-altitude resident group, each completing the MFT-M task once. Study 2 was a controlled HBO intervention study in which newcomers who had lived at a high altitude for two years were randomly divided into the HBO group (n=28) and control group (n=28). 15 times hyperbaric oxygen interventions were performed in the HBO group. Subjects in both groups completed the MFT-M task once before and once after the intervention.Results: Study 1 showed that CCC was significantly higher in the low-altitude resident group than in the high-altitude newcomer group (p=.031). Study 2 showed that the CCC in the HBO group was significantly higher after 15 hyperbaric interventions than before (p=.005), while there was no significant difference in the control group (p=.972). The HBO group had significantly higher correct task rates than the control group after the intervention (p=.001).This study confirms that long-term high-altitude exposure leads to impairment of CCC in high-altitude newcomers and that hyperbaric oxygen intervention is effective in improving CCC.